A phase field model for martensitic transformations with a temperature‐dependent separation potential. Issue 1 (October 2016) - Schmidt, Simon; Plate, Carolin; Müller, Regina; Müller, Ralf; Meiser, Jerome; Urbassek, Herbert M
Abstract: Metallic materials often exhibit a complex microstructure with varying material properties in the different phases. Of major importance in mechanical engineering is the evolution of the austenitic and martensitic phases in steel. The martensitic transformation can be induced by heat treatment or by plastic surface deformation at low temperatures. A two dimensional elastic phase field model for martensitic transformations considering several martensitic orientation variants to simulate the phase change at the surface is introduced in [1]. However here, only one martensitic orientation variant is considered for the sake of simplicity. The separation potential is temperature dependent. Therefore, the coefficients of the Landau polynomial are identified by results of molecular dynamics (MD) simulations for pure iron [1]. The resulting separation potential is applied to analyse the mean interface velocity with respect to temperature and load. The interface velocity is computed by use of the dissipative part to the configurational forces balance as suggested in [3]. The model is implemented in the finite element code FEAP using standard 4‐node elements with bi‐linear shape functions. (© 2016 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)